2020
DOI: 10.2196/17522
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Social Network–Based Smoking Cessation Intervention for Chinese Male Smokers: Pilot Randomized Controlled Trial

Abstract: Background Around 2 million Chinese people, mostly men, die annually from tobacco-related diseases; yet, fewer than 8% of Chinese smokers ever receive any smoking cessation support. Objective This study aimed to test the preliminary effectiveness and feasibility for a mobile social network (WeChat)–based smoking cessation intervention (SCAMPI program) among Chinese male smokers. Methods Chinese male smokers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
1
25
1
Order By: Relevance
“…Our results were similar to those from two recent negative randomized trials of BCW-informed interventions, one delivering thrombolytic therapy for stroke in Australia ( 53 ) and the other promoting physical activity among adults at risk for cardiovascular disease in the Netherlands ( 54 ). Similar to our experience, the authors of these studies found the BCW framework to be feasible and useful for rigorously selecting and specifying implementation components, as have other investigators planning trials of novel BCW-informed strategies to promote smoking cessation in China ( 55 ), encourage physical activity among adolescent girls in Ireland ( 56 ), and reduce sedentary behaviors at work in England ( 57 ). The two groups that observed implementation failures, the Australian thrombolytic therapy group and the Dutch physical activity group, identified challenges with implementation fidelity and a compressed implementation period as factors that limited engagement of the health care workers whom their implementation strategies targeted.…”
Section: Discussionsupporting
confidence: 52%
“…Our results were similar to those from two recent negative randomized trials of BCW-informed interventions, one delivering thrombolytic therapy for stroke in Australia ( 53 ) and the other promoting physical activity among adults at risk for cardiovascular disease in the Netherlands ( 54 ). Similar to our experience, the authors of these studies found the BCW framework to be feasible and useful for rigorously selecting and specifying implementation components, as have other investigators planning trials of novel BCW-informed strategies to promote smoking cessation in China ( 55 ), encourage physical activity among adolescent girls in Ireland ( 56 ), and reduce sedentary behaviors at work in England ( 57 ). The two groups that observed implementation failures, the Australian thrombolytic therapy group and the Dutch physical activity group, identified challenges with implementation fidelity and a compressed implementation period as factors that limited engagement of the health care workers whom their implementation strategies targeted.…”
Section: Discussionsupporting
confidence: 52%
“…However, such communication in a public group carries a potential privacy risk. In a study by Chen et al [ 35 ], 80 people were randomly allocated to 1 of 2 groups: intervention and control. The intervention group was given the entire Chinese smoking cessation plan, which was based on applicable guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, mobile interventions for smoking cessation in low- and middle-income countries have been shown to be feasible and acceptable [ 18 , 19 ]. We anticipate that the culturally tailored M2Q2 intervention will promote tobacco cessation and treatment uptake in smokers in Vietnam.…”
Section: Discussionmentioning
confidence: 99%